1996
DOI: 10.1002/ana.410390513
|View full text |Cite
|
Sign up to set email alerts
|

A newly recognized autosomal dominant limb girdle muscular dystrophy with cardiac involvement

Abstract: Sixty-five members of three families with limb girdle muscular dystrophy (LGMD) underwent neurological, cardiological, and ancillary investigations. Thirty-five individuals were diagnosed as having slowly progressive autosomal dominant LGMD. Symmetrical weakness started in the proximal lower limb muscles, and gradually upper limb muscles also became affected. Early contractures of the spine were absent. Contractures of elbows and Achilles tendons were either minimal or late. Serum creatine kinase activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 49 publications
1
80
0
8
Order By: Relevance
“…They showed similar clinical features with slowly progressive limb-girdle weakness, the absence of early contractures, age-related atrioventricular cardiac conduction disturbance, and dilated cardiomyopathy (van der Kooi et al 1996;Muchir et al 2000;Kitaguchi et al 2001). Our patient in the present study was also a familial case and showed very similar clinical features as described previously.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…They showed similar clinical features with slowly progressive limb-girdle weakness, the absence of early contractures, age-related atrioventricular cardiac conduction disturbance, and dilated cardiomyopathy (van der Kooi et al 1996;Muchir et al 2000;Kitaguchi et al 2001). Our patient in the present study was also a familial case and showed very similar clinical features as described previously.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, LGMD1B is slowly progressive, with age-related atrioventricular (AV) cardiac conduction disturbance, dilated cardiomyopathy, and the absence of early contractures (van der Kooi et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…6 LGMD1A is caused by a defect in the myotilin gene. 7 LGMD1B, located at 1q11, 8 is caused by a defect in lamin A/C 9 and LGMD1C, located at 3p25, is caused by deficiency in caveolin-3. 10,11 The locus for LGMD1D, LGMD1E and LGMD1F are respectively located at 7q, 12 6q23 13 and 7q32, 14 but their genes were not yet identified.…”
Section: Introductionmentioning
confidence: 99%
“…2 LGMD1B, due to mutations in LMNA gene encoding lamin A/C on chromosome 1q21, and LGMD1E, on 6q23, are also associated with heart conduction system abnormalities, including atrio-ventricular blocks, arrhythmia, and sudden death. [3][4][5] Mutations in CAV3 gene, located on chromosome 3p25 (LGMD1D), encoding caveolin are associated with high creatine kinase (CK) levels with normal strength and distal myopathy, and usually occur in early childhood. 6 Both LGMD1D 7 and LGMD1F 8,9 loci map to chromosome 7q and do not present distinctive clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…10 Fewer than ten AD-LGMD families show allelism with Bethlem myopathy mapped to chromosomes 2q37 and 21q22. 3 and, less frequently, with facioscapulohumeral dystrophy (FSHD) mapped to 4q35 locus (www.neuro.wustl.edu/neuromuscular/musdist/ lg.html). Pedigrees not linked to any of the listed loci warrant further genetic heterogeneity.…”
Section: Introductionmentioning
confidence: 99%